2008
DOI: 10.3133/ofr20081253
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mineral Resource Assessment of Copper, Molybdenum, Gold, and Silver in Undiscovered Porphyry Copper Deposits in the Andes Mountains of South America

Abstract: Plate 1. Map showing porphyry copper deposit t racts by age, discovered deposits, and prospects in the Andes Mountains of S outh America at s cale 1:4,000,000. Separate PDF file. Plate 2. Map showing porphyry copper deposit t racts by amount of m ean estimated undiscovered copper in the Andes Mountains of S outh America at s cale 1:4,000,000.Separate PDF file. Plate 3. Map showing porphyry copper deposit t racts by density of m ean estimated undiscovered copper in metric tons/km 2 in the Andes Mountains of S o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…In particular, along the east coast of the Antarctic Peninsula there are many exposed rock outcrops containing copper ores, copper-molybdenum porphyry deposits, while in minor amounts copper was also found in metamorphic and intrusive rocks of East Antarctica and Transantarctic Mountains not covered by ice [ 91 , 92 , 93 ]. The same high copper content is present on dust from the southernmost part of South America, which together with the Antarctic Peninsula (a geological continuation of South American Andes) is part of the Andean copper province and belongs to the circum-Pacific copper belt [ 91 , 94 , 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, along the east coast of the Antarctic Peninsula there are many exposed rock outcrops containing copper ores, copper-molybdenum porphyry deposits, while in minor amounts copper was also found in metamorphic and intrusive rocks of East Antarctica and Transantarctic Mountains not covered by ice [ 91 , 92 , 93 ]. The same high copper content is present on dust from the southernmost part of South America, which together with the Antarctic Peninsula (a geological continuation of South American Andes) is part of the Andean copper province and belongs to the circum-Pacific copper belt [ 91 , 94 , 95 , 96 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the best known and largest study of this type is the United States Geological Survey's Global Mineral Resource Assessment Project, which is being undertaken to assess the world's undiscovered non-fuel mineral resources. One of the first studies completed was a quantitative mineral resource assessment of copper, molybdenum, gold and silver in undiscovered porphyry deposits of the Andean mountain belt in South America (Cunningham et al, 2008). This study concluded that there may be a huge amount of copper to be discovered to a depth of one kilometre below the Earth's surface in the Andes, equivalent to 1.3 times as much as has already been found in porphyry copper deposits in this region.…”
Section: Geological Assessmentmentioning
confidence: 84%
“…Thus, in aggregate, 1.3 billion tons of copper have been dis covered in the Andes. In addition to copper, the cur rently unopened deposits contain molybdenum (20 million tons), gold (13 000 t), and silver (250 000 t) [6]. These results will stimulate the development of exploration not only in the Andes and neighboring areas but also in the volcanic-plutonic belts of the Pacific Rim, which, in turn, will make it possible to renew regional resources of copper-porphyry and gold-silver deposits in the future.…”
Section: The Exploration Degree Of the Volcanic-plutonic Belts Of Thementioning
confidence: 96%
“…Recently, an international research group evalu ated the forecast copper, molybdenum, gold, and sil ver resources of the currently unopened copper-por phyry deposits of the Andean Province of South America [6]. The researchers calculated that there were 69 known copper-porphyry deposits in the Andes plus 145 unopened ones.…”
Section: The Exploration Degree Of the Volcanic-plutonic Belts Of Thementioning
confidence: 99%